2021
DOI: 10.3390/sym13040624
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving and Economic Evaluations of Exhaust Waste Heat Recovery Hot Water Supply System for Resort

Abstract: The objective of this study is to investigate the energy savings and economics of the hot water supply system for the luxury resort. The hot water was generated using the waste heat from the exhaust gas heat (EGH) of internal combustion engine (ICE) installed at the luxury resort. The capacity and characteristics of waste heat source, flow demand and supply system of hot water were surveyed, and data is collected from the real system. The new heat exchanger system which utilizes the EGH to produce the hot wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The continuous combustion of fossil fuels to meet this energy demand has continued to cause progressive destruction of the environment through Greenhouse Gas (GHG) emissions. Numerous strides have been made toward minimizing the quantity of heat discarded into the environment, to reduce the carbon footprint and improve process economics [ 2 , 3 ]. To reduce excessive dependence on the use of fossil fuels to attenuate the impact of associated environmental pollutants, Woolley et al [ 4 ] suggested that manufacturers should give priority to both renewable energy systems and WHR technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous combustion of fossil fuels to meet this energy demand has continued to cause progressive destruction of the environment through Greenhouse Gas (GHG) emissions. Numerous strides have been made toward minimizing the quantity of heat discarded into the environment, to reduce the carbon footprint and improve process economics [ 2 , 3 ]. To reduce excessive dependence on the use of fossil fuels to attenuate the impact of associated environmental pollutants, Woolley et al [ 4 ] suggested that manufacturers should give priority to both renewable energy systems and WHR technologies.…”
Section: Introductionmentioning
confidence: 99%
“…There are hotels, resorts, and motels rendering services to tourists and travellers, which are strategically sited in remotely quiet and clean environments such as forests, islands, and coastlines that are far away from the power grids. To keep the guests comfortable, there is a need to meet their usual demands such as the provision of electricity and hot water, and ICEs are mainly used to actualize such [ 3 ]. For business owners to reduce operation costs due to excessive fuel consumption and at the same time help to minimize environmental footprint, WHR techniques are a viable option.…”
Section: Introductionmentioning
confidence: 99%